Chiral symmetry restoration and the critical end point in QCD - Morones Ibarra, José Rubén; Enriquez Perez Gavilan, Armando; Rodriguez, Abraham Israel Hernández; Flores Baez, Francisco Vicente; Mata Carrizalez, Nallaly Berenice; Ordoñez, Enrique Valbuena (2017)
Abstract: In a system of quark matter we study the chiralphasetransition,thebehaviorofthechiralandquark number susceptibility and the CEP at finite temperature andchemicalpotential.Thisisdonewithintheframework oftwo-flavorNambuandJona-Lasiniomodel.Wehavecalculatedthechiralquarkcondensateandthequarknumber densityand,withthis,wehavefoundthephasetransition type.Withthesequantitieswehavedeterminedthephase diagramforQCDandtheCEP. Keywords:chiralphasetransition,criticalendpoint,dynamicalmass,criticalbehavior,dynamicalchiralsymmetrybreaking